THE PERFORMANCE OF THE MANAGER IN THE HOSPITAL UNIT - Santos Freitas Leboreiro, Márcia (Health and Society, 2023)
This Article aims to interpret positive and negative points in interpersonal relationships between employees of a Hospital Unit, providing quality of life from the relationship between colleagues, direct and indirect managers, employees and patients, analyzing the functions in the Hospital Unit. In order to carry out this Article, bibliographic surveys and Consultations of Periodical Materials, Magazines and Sites specialized in the subject were necessary for reflection on People Management in a Hospital Unit. The methodology used was the literature in Portuguese from 2003 to 2009. In these materials, I encounter numerous challenges that were faced by managers and workers, which implies collectively (re)thinking the ways of planning, organizing and operating care in Health Management in the Hospital Unit. Understand the possibilities of People management actions in leading the multidisciplinary team in a cohesive way, allowing the work to flow satisfactorily with a focus on improving the quality of medical and hospital care. Understanding that functions in the Hospital Unit, pervades the stimulation of positive productivity, working in continuing education, valuing self-esteem, interacting and demonstrating professional recognition by promoting well-being to the worker, environmental, instrumental, motivational conditions including promotions and awards, collaborating for the growth of the institution and the professional himself.